The magnetic properties of MAl4(OH)12SO4·3H2O with M = Co2+, Ni2+, and Cu2+ determined by a combined experimental and computational approach. Issue 4 (11th January 2023) - Andersen, Anders B. A.; Christiansen, Rasmus Tang; Holm-Janas, Sofie; Manvell, Anna S.; Pedersen, Kasper S.; Sheptyakov, Denis; Embs, Jan Peter; Jacobsen, Henrik; Dachs, Edgar; Vaara, Juha; Lefmann, Kim; Nielsen, Ulla Gro
Abstract : CoAl4 (OH)12 (SO4 )·3H2 O is a 0D magnet and MAl4 (OH)12 (SO4 )·3H2 O with M = Ni 2+ and Cu 2+ are ferromagnetic spin chains (no magnetic ordering > 2 K) based on magnetic susceptibility, neutron scattering, NMR, and first-principles calculations. Abstract : The magnetic properties of the nickelalumite-type layered double hydroxides (LDH), MAl4 (OH)12 (SO4 )·3H2 O (MAl4 -LDH) with M = Co 2+ ( S = 3/2), Ni 2+ ( S = 1), or Cu 2+ ( S = 1/2) were determined by a combined experimental and computational approach. They represent three new inorganic, low-dimensional magnetic systems with a defect-free, structurally ordered magnetic lattice. They exhibit no sign of magnetic ordering down to 2 K in contrast to conventional hydrotalcite LDH. Detailed insight into the complex interplay between the choice of magnetic ion (M 2+ ) and magnetic properties was obtained by a combination of magnetic susceptibility, heat capacity, neutron scattering, solid-state NMR spectroscopy, and first-principles calculations. The NiAl4 - and especially CoAl4 -LDH have pronounced zero-field splitting (ZFS, easy-axis and easy-plane, respectively) and weak ferromagnetic nearest-neighbour interactions. Thus, they are rare examples of predominantly zero-dimensional spin systems in dense, inorganic matrices. In contrast, CuAl4 -LDH ( S = 1/2) consists of weakly ferromagnetic S = 1/2 spin chains. For all three MAl4 -LDH, good agreement is found between the experimental magnetic parameters ( J, D, g ) and first-principles quantum chemical calculations, which also predict that the interchain couplings are extremely weak (< 0.1 cm −1 ). Thus, our approach will be valuable for evaluation and prediction of magnetic properties in other inorganic materials.